Operations management for competitive advantage - Chase, Richard B. (McGraw-Hill, 2006)
Richard B. Chase is Director of the Center for Operations Management Research and Education at USC. He is widely published in both books and academic journals and is considered one of the top service "gurus" in the field. He is on the Editorial Advisory Board of the Journal of Operations Management, an Advisor to Production and Operations Management journal, and a Fellow of the Decision Sciences Institute. F. Robert Jacobs is currently department chairman at Indiana University. He has a PH.D from Ohio State and is past Vice President of the Decision Sciences Institute, Information Technology Coordinator for Decision Sciences Institute for 1997, as well as Associate Editor on the board of the Journal of Operations Management